Características clínicas e assistenciais de crianças com sibilância/asma atendidas na rede de saúde do município de Fortaleza - Castro, Perpétua Maria Eduardo Bezerra de (2006)
Asthma is the most ordinary chronic disease in childhood, and it is characterized by presenting recurrent episodes of wheezing and, most of time, by the need of planned and continued care in order to control it. AIMS To describe clinical and aiding features of children with wheeze/asthma who are users of health services in Fortaleza. METHOD Transversal study, proceeded with data obtained from patient records employed in the admittance of asthmatic children within Integral Care to Children`s Healt Program (Programa de Atenção Integral à Saúde da Criança – PROAICA). Were selected 930 children from 2 months to 16 years-old who have been seen from June of 2004 to September of 2005, in nine primary health care facilities (PHCFs) and two hospitals. The primary variable studied was how long the wheezing child stayed without planned assistance until the moment of her admission in the Program. RESULTS The mean time children stayed unassisted was 49 months. (DP=38,1). 90,2% of children presented first symptoms of wheeze before the age of three years (mean= 16 months). In the last year, before admittance in the Program, the proportion of children who went to the ER was 91,4%, and 42,3% were multiply hospitalized. 98,1% arrived in use of relieving medication with oral administration and only 4,3% were using inhaled corticosteroid. CONCLUSIONS Children with wheeze/asthma for a very long time without planned assistance by health services web was the primary found in this study. Most of children presented the first crisis with age under 3 years and, nevertheless, they stayed for a long without planned assistance, which contributed to their recurring in-hospital assessments within the ERs with several hospitalizations. Such setting shows the need for an appropriate integral care to the health of asthmatic child.